2005
DOI: 10.1529/biophysj.104.053421
|View full text |Cite
|
Sign up to set email alerts
|

Homology Modeling and Molecular Dynamics Simulations of Transmembrane Domain Structure of Human Neuronal Nicotinic Acetylcholine Receptor

Abstract: A three-dimensional model of the transmembrane domain of a neuronal-type nicotinic acetylcholine receptor (nAChR), (alpha4)2(beta2)3, was constructed from a homology structure of the muscle-type nAChR recently determined by cryo-electron microscopy. The neuronal channel model was embedded in a fully hydrated DMPC lipid bilayer, and molecular-dynamics simulations were performed for 5 ns. A comparative analysis of the neuronal- versus muscle-type nAChR models revealed many conserved pore-lining residues, but an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
35
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 62 publications
(68 reference statements)
10
35
0
Order By: Relevance
“…Henchman et al studied the dynamics of the ligand-binding domain of the human a7 nicotinic receptor, and observed asymmetrical motions in the presence of different ligands [20]. MD simulations of the transmembrane domain investigated the dynamics of the M2 helices [21][22][23], the importance of the hydrophobic gates [24,25], and the lipid-M4 interactions [26]. More recently, a simulation on the human a7 nAChR with both the ligand-binding and transmembrane domains revealed that the protein undergoes a twist-to-close motion that correlates movements of the Cloop with the rotation and inward movement of two nonadjacent subunits [27].…”
Section: Introductionmentioning
confidence: 99%
“…Henchman et al studied the dynamics of the ligand-binding domain of the human a7 nicotinic receptor, and observed asymmetrical motions in the presence of different ligands [20]. MD simulations of the transmembrane domain investigated the dynamics of the M2 helices [21][22][23], the importance of the hydrophobic gates [24,25], and the lipid-M4 interactions [26]. More recently, a simulation on the human a7 nAChR with both the ligand-binding and transmembrane domains revealed that the protein undergoes a twist-to-close motion that correlates movements of the Cloop with the rotation and inward movement of two nonadjacent subunits [27].…”
Section: Introductionmentioning
confidence: 99%
“…The salt bridges could last for several nanoseconds, and sometimes two salt bridges could be formed simultaneously. Detailed analyses [10] indicate that the extracellular mouth of the pore has the narrowest radius, but this physical restriction does not occlude the water passage in this region of the pore. The energy barrier restricting the water passage occurs almost two helix turns into the channel at a hydrophobic girdle formed by a4-Val 259 and a4-Leu 263 and the analogous h2-Val 253 and h2-Leu 257 , which may act as a hydrophobic gate to ion permeations.…”
Section: Tm Domains Of Glycine Receptor and Neuronal Acetylcholine Rementioning
confidence: 97%
“…The details of the studies discussed below have been published elsewhere [8][9][10][11][12][13][14][15]. Here we give an overview of the major conclusions from these studies.…”
Section: Recent Structure and Dynamics Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a typical RMSF pattern, a low RMSF value indicates the well-structured regions while the high values indicate the loosely structured loop regions or domains terminal 45 . As shown in Figure 3, the major backbone fluctuation was seen to occur in the loop regions, whereas regions with low RMSF correspond exclusively to the rigid beta-alpha-beta fold.…”
Section: Root Mean Square Fluctuation (Rmsf) Of Ca Atoms By Residuesmentioning
confidence: 99%